2009
DOI: 10.1039/b822408k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fixation on in vitro cell culture lines monitored with Raman spectroscopy

Abstract: Raman spectroscopy provides chemical-rich information about the composition of analytes and is a powerful tool for biological studies. With the ability to investigate specific cellular components or image whole cells, compatible methods of sample preservation must be implemented for accurate spectra to be collected. Unfortunately, the effects of many commonly used sample preservation methods have not been explored with cultured cells. In this study, two human cell lineages of varying phenotypes were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 53 publications
(60 reference statements)
2
79
0
1
Order By: Relevance
“…Nevertheless, formalin xation has been found to be the best method for preserving cellular integrity with a weak impact on the overall molecular content and yielding the spectral prole closest to that observed in the live state, while hardly affecting discrimination between cells under distinct conditions (namely control and drugexposed). 31,[56][57][58] No formalin contamination was veried in the measured spectral data, with no signals being detected for its typical t(CH 2 ), n(CO) and d(CH 2 ) modes at ca. 907, 1040 and 1490 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, formalin xation has been found to be the best method for preserving cellular integrity with a weak impact on the overall molecular content and yielding the spectral prole closest to that observed in the live state, while hardly affecting discrimination between cells under distinct conditions (namely control and drugexposed). 31,[56][57][58] No formalin contamination was veried in the measured spectral data, with no signals being detected for its typical t(CH 2 ), n(CO) and d(CH 2 ) modes at ca. 907, 1040 and 1490 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with numerous previous studies which report only slight modications of the spectra aer formalin xation 16,19,23,26,29,30 but contradict few others which attribute large spectral changes to xation protocols. 25,27 Various studies indicate that other xation methods used for the preservation of biological tissues inuence similarly or even more the cell IR spectra. For instance, xatives like acetone or ethanol are shown to inuence more considerably the IR spectra of cells than formalin-xation.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 Previous studies have been carried out in order to describe the inuence of formalin-based xation and paraffin preservation on spectral features of tissues and cells with both infrared and Raman spectroscopy. 16,19,[23][24][25][26][27][28][29][30] While some studies report only a slight impact of formalin xation on the spectra, 26,[28][29][30] other studies observed important modications concerning the cellular lipid and protein content.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the introduction, polystyrene based substrates and glass slides should be avoided for Raman spectroscopy. Although quartz is commonly used to grow the cells; it has been decided to opt for CaF 2 windows for the realization of this work in order to reduce as much as possible the contribution of the substrate in the spectra recorded [20,21] .…”
Section: Resultsmentioning
confidence: 99%